2018
DOI: 10.3389/fmars.2018.00415
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Retention in the Swedish Coastal Zone

Abstract: In this study, the average nutrient filter efficiency of the entire Swedish coastline is estimated to be about 54 and 70% for nitrogen and phosphorus, respectively. Hence, significantly less than half of the nutrient input from land (defined as river discharge and point sources) can be assumed to be exported from coastal waters to the open sea. However, some coastal areas retained more than 100% of the land load and thus, also filter the open Baltic Sea water. These areas with effective filtering of nutrients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 37 publications
1
27
0
1
Order By: Relevance
“…Data derived from the Swedish National Oceanographic Data Centre nitrogen derived from riverine runoff and from filamentous cyanobacteria are where it enters the water. For example, along the Baltic Sea coastline, biogeochemical processes remove nitrogen from riverine input by 50-100% (Edman et al 2018), and all of it therefore does not reach open Baltic Sea. While denitrification is a process capable of removing reactive nitrogen from a system, it is unlikely that denitrification is a significant sink of nitrogen in welloxygenated offshore water columns (Edman et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Data derived from the Swedish National Oceanographic Data Centre nitrogen derived from riverine runoff and from filamentous cyanobacteria are where it enters the water. For example, along the Baltic Sea coastline, biogeochemical processes remove nitrogen from riverine input by 50-100% (Edman et al 2018), and all of it therefore does not reach open Baltic Sea. While denitrification is a process capable of removing reactive nitrogen from a system, it is unlikely that denitrification is a significant sink of nitrogen in welloxygenated offshore water columns (Edman et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This retention timescale constrains coast-ocean exchanges and allows for biogeochemical processes to impart their unique signatures on coastal environment. It has been shown that coastal retention may enhance productivity (Edman et al, 2018;Lohrenz et al, 1999), favor recruitment of larval fish (Mullaney & Suthers, 2013), constrain connectivity between coral reefs (Figueiredo et al, 2014), and facilitate development of harmful algal blooms (Pitcher et al, 2010) and coastal hypoxia Rabalais et al, 2014). Coastal retention and coast-ocean exchanges are also key to the role that the coastal ocean plays in the global carbon cycle.…”
Section: Introductionmentioning
confidence: 99%
“…The sub-basins are identical to the defined national water body classification according to the EU WFD and are described by their hypsographical curve [44]. Recently, the SCM was used to simulate and describe coastal nutrient retention around Sweden [45], and had previously been used for a similar study in the Stockholm archipelago [46]. Both studies have shown that SCM skill to calculate the average state (average vertical profiles and mean seasonal variations) in coastal water bodies is usually good, or acceptable.…”
Section: Derived Water Quality Estimates From the Swedish Coastal Zonmentioning
confidence: 99%
“…For this current study we apply the same cost function (for the same type of data distributions) as in the previous studies [45,46] to evaluate the proximity of the average model states to the average of in situ measurements at three locations in Bråviken. The proximity is evaluated by normalizing the bias between model (P) to observations (O) with the standard deviation of the observations, i.e.,…”
Section: Derived Water Quality Estimates From the Swedish Coastal Zonmentioning
confidence: 99%
See 1 more Smart Citation